Gold recovery from waste electrical and electronic equipment by electrodeposition: A feasibility study - Lekka, M.; Masavetas, I.; Benedetti, A. V. [UNESP]; Moutsatsou, A.; Fedrizzi, L. (Elsevier B.V., 2015)
Due to rapid technological progress, the replacement of electronic equipment is very often necessary, leading to huge amounts that end up as waste. Printed circuit boards (PCBs) constitute a unique section among Waste Electrical and Electronic Equipment (WEEE), due to their content in precious and high commercial value metals. Gold, among them, is usually present in a very low quantity and its recovery requires complex chemical treatments. The aim of this work is to evaluate the feasibility of recovering Au by electrodeposition from aqueous solutions obtained after leaching of PCBs and electrical contacts prior to the recovery of any other metals. Aqua regia was used as a leachant for the powders obtained after mechanical and thermal treatment of PCBs' and contacts' parts. The leaching solutions have been analysed by ICP in order to detect the most important metals for the electrodeposition. A preliminary study using synthetic solutions of the elements which could interfere with the gold deposition was performed, followed by an electrochemical study of leach solution of PCBs and contacts. The deposition potential of gold was determined in each solution and a short potentiostatic deposition was carried out. The obtained deposits have been observed by SEM and analysed by EDXS in order to confirm the deposition and to evaluate the purity of the obtained deposits. Aqua regia was proved to be an efficient leachant for the dissolution of all metals from powders obtained after thermal treatment of PCBs and contacts. Among the metals present in the leach solution only copper can interfere with the deposition of gold as the reduction peaks of the auric chloride complex and the Cu2+ ions are very close. However, the deposition of Au was possible, even with low efficiency. The deposition rate increases by increasing the temperature at 40 degrees C and the stirring of the electrolyte. A compact nanocrystalline deposit of high purity gold has been obtained by electrodeposition at 0.55 V vs. Ag/AgCl/KCl3M from the contacts' leach solution. Therefore, this study demonstrates the feasibility of gold recovery from PCBs' and contacts' leach solutions by electrodeposition, without any further chemical treatment. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Gold recovery; Electrodeposition; Leaching; PCBs